Current Challenges in Risk Management : a comparative study from organizations in the energy sector - Karban, Jan; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
This master thesis deals with the use of risk management and its techniques in the companies in the energy sector. The main objective is to evaluate the use of the methods and the approach of risk management used in companies compared to the theoretical research. The first chapter introduces the word risk, its origin, definition and classification followed by the description of risk management and its process as well as the development of the discipline. Next the energy sector specification is laid out and the importance of risk management in such industry explained. Through interviews with representatives from different companies the insights of the way risk management is done in the companies was presented and compared. While the theory highlights the importance of holistic risk management, the research discovered, that while there is a deep connection between strategy and risk management and the setting in each company is highly tailored to its needs, the practical situation does follow the theory only partially.
Vedoucí práce: Karel Janda
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses